Spanish Fund : financial statement
1936-09-02 SPANISH FUND. £. s. d. Total received fron sources in Great Britain ................... 11,739. 0. 8. Total received from America ....... 6,954. 5. 9. Transferred to the International Federation of Trades Union's Account ........................£ 15,000. 0. 0. 2/9/36. 292/946/10/119